Structural and functional traits mediating the adaptability of creeping signal grass [Urochloa reptans (L.) Stapf] across diverse ecozones - Rehman, Hafeez ur; Ahmad, Farooq; Hameed, Mansoor; Shafqat, Jazab; Warraich, Ejaz Ahmad; Haider, Arslan; Yaseen, Saba; Ramzan, Tahrim; Raza, Ali (International Journal of Applied and Experimental Biology, 2026)
Plants of the genus Urochloa P. Beauv., popularly known as brachiaria, or marmalade grass, belong to the family Poaceae. Urochloa reptans is a member of the genus Urochloa and is also known as creeping signal grass. It is widely distributed in tropical and subtropical regions of the world. The present experiment explored the anatomical, structural, functional, and physiological adaptive features of Urochloa reptans sampled from sixteen different sites of the Faisalabad region, Pakistan. All the collected populations showed numerous anatomical modifications, and also possess marked physiological characteristics that help them to survive under varying ecological conditions. This leads to their ecological success for existence in heterogeneous environments. The populations of Eden Garden and Canal Road had maximum leaf epidermal thickness, while midrib thickness was higher in the Manawala ecotype. The bulliform cell area was noted to be widened mainly in the Narwala Bangla population. The intensive sclerification of the stem was observed in a sample of Makkuana. The populations from Painsra and Eden Garden possessed larger vascular bundle areas. However, only the Eden Garden population exhibited a larger metaxylem area. The populations native to Canal Road and Sadar Bypass exhibited vigorous root growth in terms of cortical region thickness, endodermal thickness, and pith cell area. Besides this, well-developed aerenchyma cells and metaxylem vessels were observed in the Canal Road and Chicha populations. Overall, U. reptans showed much outstanding activity in the context of development, structural, functional, and physiological characteristics in response to the present-day ecological scenario.